Pengembangan algoritma sederhana Kardiotokografi untuk Baseline Denyut Jantung Janin (DJJ) Menggunakan Matlab - Ariep Jaenul; Dewi Rahmawati; Shahad Alyousif (Universitas PGRI Kanjuruhan Malang, 2022)
Interpretation of Cardiotocography (CTG) performed using a computer can assist the interpretation made by obstetricians. The main objective of this study was to develop a simple algorithm for the development of baseline Fetal Heart Rate feature extraction based on RCOG guidelines. The proposed algorithm was developed using the Matlab application. The results obtained showed that the baseline fetal heart rate feature classification got very good results and was validated by the interpretation obtained from the obstetrician.